Demand for global health training among obstetrics and gynaecology trainees in Australia and New Zealand: Insights from the TIGHT study. (29th January 2020) - Mitchell, Rebecca; Mitchell, Rob; Phillips, Georgina; Jayaratnam, Skandarupan
Abstract : Background: Global health (GH) training aims to equip clinicians with the skills and knowledge to practise in international and cross‐cultural environments. Interest among obstetrics and gynaecology trainees is unknown. Aims: The Trainee Interest in Global Health Training (TIGHT) study aimed to assess demand for GH training among specialty trainees in Australia and New Zealand. The primary objective was to quantify the number of trainees interested in undertaking a rotation in a resource‐limited environment (RLE) in a low‐ or middle‐income country during specialty training. This paper reports the results of a planned sub‐group analysis of Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) trainees. Materials and Methods: A cross‐sectional study was conducted between August and October 2018. Data were collected using an anonymous, self‐reporting, web‐based survey. Results: There were 210 respondents among 698 RANZCOG trainees, equating to a response rate of 30.1%. Overall, 77% (157/204) of respondents were keen to undertake a rotation in a RLE, with the vast majority (166/203, 81.8%) interested or very interested in having their GH accredited for training. Sixty‐four percent (125/195) expressed interest in undertaking an integrated GH training or fellowship program as an adjunct to specialty training, and a majority (177/201, 88.1%) were keen to continue GH work as a specialist obstetrician and gynaecologist. Conclusion: There is significant demand for GH training among RANZCOG trainees. These findings should inform the development of accredited rotations in RLEs and the cultivation of safe and effective global women's health training pathways. Ideally, these arrangements should be underpinned by mutually beneficial partnerships with both educational and development objectives.